EFFECTS OF PHYSICAL EXERCISE ON GENERALIZED ANXIETY DISORDER - dos Santos Alves, Ana Lucia; Borges Lima de Castro, Cássia (Cadernos ESP, 2024)
To identify the effects and possible benefits of physical exercise in individuals with generalized anxiety disorder who use controlled medication, in the perception of the participants. It was characterized as descriptive, exploratory, field research. It used the quantitative-qualitative method, of an applied nature. Participants were individuals aged 18 and 64 with TAG from Quixadá/Ce, using controlled medication and practicing physical exercise for at least 6 months. Data were collected through interviews. The analysis used Excel and the Content Analysis technique. Participants showed improved mood, decreased agitation, help with sleep, greater willingness to carry out daily activities and reduced disordered thoughts. It is concluded that the prescription of physical exercise for patients with anxiety disorder was positive in the view of participants who used physical exercise as a complement to drug treatment.
Keywords: Physical Exercise; Physical Activity; Generalized Anxiety Disorder